Menghadapi Kejahatan Seksual terhadap Anak: Analisis Penanganan oleh Kepolisian: Addressing Sexual Crimes Against Children: An Analysis of Police Handling - Adam, Marlan; Imran, Suwitno Yutye; Mandjo, Julius T (Jurnal Hukum Bisnis, 2026)
Sexual crimes against children are a complex legal and social issue because they involve victims with a high level of vulnerability and require a sensitive and comprehensive law enforcement response. This study aims to analyse police efforts in handling child molestation crimes by taking an empirical approach at the North Gorontalo Police Resort. The study used an empirical legal method with a juridical-sociological approach. Data were obtained through interviews with police officers, limited observations of the case handling process, and a literature review of relevant laws and regulations and scientific literature. The results show that the police have implemented various preventive and repressive efforts in handling child molestation cases, including legal counselling, cross-sector coordination, and investigative processes in accordance with legal procedures. However, the effectiveness of handling still faces structural, cultural, and technical obstacles, such as limited evidence, minimal supporting resources, and social pressures that affect the continuity of the legal process. This study confirms that the success of handling sexual crimes against children is not only determined by the existence of regulations, but is highly dependent on institutional capacity, the quality of human resources, and the integration of the child protection system. It is hoped that the research findings will serve as a basis for strengthening law enforcement policies and practices that are more oriented towards the best interests of children.